Enterprise-Wide Risk Management (EWRM) implementation, compliance and value creation among Public Listed Companies (PLCs) in Malaysia / Norlida Abdul Manab - Abdul Manab, Norlida (2009)
The Enterprise-Wide Risk Management (EWRM) concept seems to be gaining ground worldwide. Although this concept is still new in many parts of Asia, and Malaysia in particular, there are positive indications that EWRM is beginning to receive much attention, and that this topic is being widely discussed on an industry-wide basis. Numerous studies on this concept have been done by the practitioners, consultant firms, and professional bodies, rather than by academicians. The emergence of EWRM is cited to be driven most by corporate governance, and its effective implementation is claimed to contribute toward value creation. However, there is still lack of evidence of EWRM practices and their relationships with value creation.